ENGLISH LANGUAGE TEACHING IN INDONESIA AND ITS RELATION TO THE ROLE OF ENGLISH AS AN INTERNATIONAL LANGUAGE - Zananda, Tiray Febria (Prodi Pendidikan Bahasa Inggris Universitas Palembang, 2023)
Since Indonesia is categorized as an English Foreign Language (EFL)country, it is interesting to find out whether this issue has an impact onEnglish Language Teaching practices in this country. This articledescribes general trends of English Language Teaching in Indonesialast few decades and discusses whether rapid globalization of Englishhas any significant impact on English as an International Language(EIL) policy and practices in this country, and also whether newtrends in English as an International Language (EIL) influenceperception of and toward English in this country.